Extracellular HMGB1 Induced Glomerular Endothelial Cell Injury via TLR4/MyD88 Signaling Pathway in Lupus Nephritis - Tian Yu; Feng Xiaojuan; Liu Jinxi; Miao Xinyan; Xu Jie; Tian Yuexin; Liu Qingjuan; Zhang Wei; Gu Cunyang; Huang Jie; Wu Lunbi; Zhao Hang; et al. (Mediators of Inflammation)
Previously, our study showed that HMGB1 was significantly elevated in the blood and located in the glomerular endothelium in LN patients. But whether extracellular HMGB1 is involved in the injury of glomerular endothelial cells (GECs) in LN still needs further investigation. Firstly, we detected the levels of SDC-1, VCAM-1, and proteinuria in LN patients and MRL/lpr mice and analyzed their correlations. Then, HMGB1 and TLR4/MyD88 were inhibited to observe the shedding of glycocalyx and injury of GECs in vivo and in vitro. Our results showed that HRGEC injury and SDC-1 shedding played an important role in the increase of permeability and proteinuria formation in LN. Additionally, inhibition of extracellular HMGB1 and/or downstream TLR4/MyD88/NF-κB/p65 signaling pathway also alleviated GEC monolayer permeability, reduced the shedding of the glomerular endothelial glycocalyx, improved the intercellular tight junction and cytoskeletal arrangement, and downregulated the NO level and VCAM-1 expression. These results suggested that extracellular HMGB1 might involve in GEC injury by activating the TLR4/MyD88 signaling pathway in LN, which provided novel insights and potential therapeutic target for the treatment of lupus nephritis.